TANGGUNGJAWAB NOTARIS ATAS ISI PERJANJIAN PERKAWINAN SETELAH PERKAWINAN - Ane Fany Novitasari (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
Abstract Journal writing is to discuss the responsibilities of a notary for the content of the marriage covenant after marriage. The purpose of this study, to describe and analyze the responsibility of the notary on the amendment of marriage after the course of the marriage and the legal consequences after changes on the marriage covenant. The research method used in writing this journal is a normative legal research. The approach used is the approach of legislation, the conceptual approach, and the approach to the case. The research result of this journal is the responsibility of the Notary deed he made related to the change of the marriage covenant, which is the responsibility of civil Notaries provide limited information because the case goes in the administrative area, in the case of positions 526 / Pdt.G / 2012 / PN.Jkt .Cell. While in Law Notary, the Notary Responsibility deed made notaries is the responsibility borne by the office. The legal consequences following an amendment to the covenant of marriage that in the case of positions 526 / Pdt.G / 2012 / PN.Jkt.Sel amendment to the marriage settlement agreement resulted marriage certificate null and void due to not meet the objective requirements associated with Article 1320 of the Civil Code, namely causa kosher as well as the Second Party assert and defend himself, the right to organize and the right to to take care of their own property, both movable items or goods not moving and are free to pick flowers, fruit or result of wealth, job and from the source other-source without requiring assistance, approval or authorization from the first, and all costs and fees as well as all expenditures for household purposes and interests, including expenses incurred by marriage and education expenses for children born from this marriage entirely the responsibility of the first party (husband). Key words: responsibillity, notary, the marriage covenant Abstrak Penulisan jurnal ini membahas mengenai mengenai tanggungjawab notaris atas isi perjanjian perkawinan setelah perkawinan. Tujuan penelitian ini, untuk mendeskripsikan dan menganalisa tanggungjawab notaris atas perubahan perjanjian perkawinan setelah berlangsungnya perkawinan dan akibat-akibat hukum setelah dilakukan perubahan atas perjanjian perkawinan. Metode penelitian yang digunakan dalam penulisan jurnal ini yaitu penelitian hukum normatif. Pendekatan yang digunakan yaitu pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan kasus. Hasil penelitian jurnal ini adalah tanggungjawab Notaris terhadap akta yang dibuatnya berkaitan dengan perubahan perjanjian perkawinan, yaitu secara perdata adalah tanggungjawab Notaris sebatas memberikan keterangan karena kasus tersebut masuk dalam wilayah administratif, pada kasus posisi No.526/Pdt.G/2012/PN.Jkt.Sel.Sedangkan di dalam Undang-undang Jabatan Notaris, Tanggungjawab Notaris terhadap akta yang dibuatnya ialah tanggungjawab notaris dibebankan kepada jabatannya. Akibat hukum setelah dilakukannya perubahan atas perjanjian perkawinan yaitu dalam kasus posisi No.526/Pdt.G/2012/PN.Jkt.Sel perubahan atas perjanjian perkawinan mengakibatkan akta perjanjian perkawinan batal demi hukum dikarenakan tidak memenuhi syarat obyektif dikaitkan dengan pasal 1320 KUHPerdata, yaitu causa yang halal serta Pihak Kedua menuntut dan mempertahankan untuk dirinya sendiri, hak untuk mengelola dan hak untuk untuk mengurus harta kekayaan sendiri, baik barang bergerak maupun barang-barang tidak bergerak dan bebas untuk memungut bunga, buah atau hasil dari kekayaanya, pekerjaannya dan dari sumber-sumber lain tanpa memerlukan bantuan, persetujuan atau kuasa dari pihak pertama, dan segala ongkos dan biaya serta semua pengeluaran untuk keperluan dan kepentingan rumah tangga termasuk beban-beban yang timbul karena perkawinan dan beban-beban untuk pendidikan anak-anak yang lahir dari perkawinan ini seluruhnya menjadi tanggungan pihak pertama (suami). Kata kunci : tanggungjawab, notaris, perjanjian perkawinan